Modes of ministry : a comparison between Anglican and Roman Catholic priests' perceptions of the priesthood and approaches to their role in the contemporary South African context - Stones, Timothy Riordan (Department of Religious Studies, 2014)
Includes bibliographical references (leaves 135-145).